2012
DOI: 10.2741/3935
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant associations of human SP-A and SP-D with acute and chronic lung injury

Abstract: Pulmonary surfactant, a lipoprotein complex, maintains alveolar integrity and plays an important role in lung host defense, and control of inflammation. Altered inflammatory processes and surfactant dysfunction are well described events that occur in patients with acute or chronic lung disease that can develop secondary to a variety of insults. Genetic variants of surfactant proteins, including single nucleotide polymorphisms, haplotypes, and other genetic variations have been associated with acute and chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
98
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 239 publications
1
98
0
5
Order By: Relevance
“…Studies of the genetics of SP-A have revealed correlations of SFTPA1 and SFTPA2 variants with lung disease susceptibility (16,58), and polymorphisms of SP-A variants have been associated with variable gene expression levels (6). variants 6A, 6A 2 , 6A 3 , and 6A 4 , as well as mutants of the 11-nt element 6Ains, 6A 2 del, 6A 3 ins, and 6A 4 ins were cotransfected in NCI-H441 cells with miRNA mimics and a Renilla luciferase control plasmid.…”
Section: Effect Of Mir-183 On Sftpa1 and Sftpa2 Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the genetics of SP-A have revealed correlations of SFTPA1 and SFTPA2 variants with lung disease susceptibility (16,58), and polymorphisms of SP-A variants have been associated with variable gene expression levels (6). variants 6A, 6A 2 , 6A 3 , and 6A 4 , as well as mutants of the 11-nt element 6Ains, 6A 2 del, 6A 3 ins, and 6A 4 ins were cotransfected in NCI-H441 cells with miRNA mimics and a Renilla luciferase control plasmid.…”
Section: Effect Of Mir-183 On Sftpa1 and Sftpa2 Gene Expressionmentioning
confidence: 99%
“…Recently, certain SP-A2 variants were associated with low levels of SP-A, and low SP-A levels were associated with poor outcome in patients with lung transplants (6). We have previously hypothesized that the SP-A functional activity depends on the relative amount of SP-A1 and SP-A2, as alterations in both total SP-A content and the SP-A1/SP-A ratio have been observed in lung secretions of patients suffering from asthma and cystic fibrosis (58,61,74). Thus it is likely that independent regulatory mechanisms control the expression of variants of SFTPA1 and SFTPA2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These variants have been associated with many lung diseases including neonatal diseases, such as Respiratory Distress Syndrome (RDS) and Bronchopulmonary Dysplasia (BPD) [11]. The SP-A1 and SP-A2 gene products have been shown to differ in several functions related to innate immunity [12] and in surfactantrelated functions [13,14].…”
mentioning
confidence: 99%
“…Because low levels of SP-A have been associated with neonatal disease (RDS, BPD) risk, as well as with risk in adult disease (IPF) or condition (lung trauma) [11], enhancing the expression of SP-A1, SP-A2, or both depending on the particular functional need may be another way to increase their levels in neonatal life. Although individuals with lung disease have been shown to have altered levels of SP-A, it is not known whether these reflect change in both gene products, or just one, and if the latter, which one.…”
mentioning
confidence: 99%